Ответ:
Пошаговое объяснение:
1) -5a²b⁴ * 4a³b⁵ = -5*4= -20
по такому же принципу решаем остальные
2) 7a¹¹b³*(-5a¹⁴b⁷) =
3) -0,3a⁵b¹¹*0,2ab¹⁴ =
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
Ответ:
Пошаговое объяснение:
1) -5a²b⁴ * 4a³b⁵ = -5*4![a^{2+3} a^{2+3}](https://tex.z-dn.net/?f=a%5E%7B2%2B3%7D)
= -20![a^{5}b^{9} a^{5}b^{9}](https://tex.z-dn.net/?f=a%5E%7B5%7Db%5E%7B9%7D)
по такому же принципу решаем остальные
2) 7a¹¹b³*(-5a¹⁴b⁷) =![-35a^{25}b^{10} -35a^{25}b^{10}](https://tex.z-dn.net/?f=-35a%5E%7B25%7Db%5E%7B10%7D)
3) -0,3a⁵b¹¹*0,2ab¹⁴ =